Characterization of the internal working-life exposome using minimally and non-invasive sampling methods - a narrative review - Verscheure, Eline; Stierum, Rob; Schlünssen, Vivi; Lund Würtz, Anne Mette; Vanneste, Dorian; Kogevinas, Manolis; Harding, Barbara N; Broberg, Karin; Narui, Shan Zienolddiny; Erdem, Johanna Samulin; Das, Mrinal K; Makris, Konstantinos C.; et al. (My University, 2023)
During recent years, we are moving away from the 'one exposure, one disease'-approach in occupational settings and towards a more comprehensive approach, taking into account the totality of exposures during a life course by using an exposome approach. Taking an exposome approach however is accompanied by many challenges, one of which, for example, relates to the collection of biological samples. Methods used for sample collection in occupational exposome studies should ideally be minimally invasive, while at the same time sensitive, and enable meaningful repeated sampling in a large population and over a longer time period. This might be hampered in specific situations e.g., people working in remote areas, during pandemics or with flexible work hours. In these situations, using self-sampling techniques might offer a solution. Therefore, our aim was to identify existing self-sampling techniques and to evaluate the applicability of these techniques in an occupational exposome context by conducting a literature review. We here present an overview of current self-sampling methodologies used to characterize the internal exposome. In addition, the use of different biological matrices was evaluated and subdivided based on their level of invasiveness and applicability in an occupational exposome context. In conclusion, this review and the overview of self-sampling techniques presented herein can serve as a guide in the design of future (occupational) exposome studies while circumventing sample collection challenges associated with exposome studies.
Keywords: Biomarker; Biomonitoring; Data availability; Exposome; Non-invasive sampling; Occupational; Self-sampling